Mogroside derivatives exert hypoglycemics effects by decreasing blood glucose level in HepG2 cells and alleviates insulin resistance in T2DM rats. (December 2019) - Liu, Xuan; Zhang, Jingjing; Li, Yumeng; Sun, Liyang; Xiao, Yao; Gao, Wenge; Zhang, Zesheng
Graphical abstract: Highlights: Different mogroside hypoglycemics' effects in HepG2 cells. Compared with others, Mogroside V had the most obvious on blood glucose decrease. Mogroside V improved blood glucose, liver damage and insulin resistance in T2DM rats. Mogroside V increased glycogen synthesis through PI3K/Akt signaling pathways. Abstract: Mogroside, a triterpenoid of Siraitia grosvenorii, has been reported to play an important role in glycometabolism processes. In this study, the mechanism of mogroside was evaluated through in vitro experiments using Mogroside III (MO3), IV (MO4), V (MO5), Siamenoside I (SO1) at 1, 5, 10 μM, and in vivo experiments using MO5 at 30, 75, 150 mg/(kg·bw·day). In cell experiments, mogrosides at 5 μM significantly restored glucose metabolism and insulin resistance (IR), and MO5 had the most obvious hypoglycemic effect. In rat experiments, fasting blood glucose, liver damage, and insulin sensitivity were improved by MO5 treatment. Moreover, the Real-Time Polymerase Chain Reaction and Western bolt analysis indicated that MO5 up-regulated the expression of phosphatidylinositol-3-kinase (PI3K), glucose transporter type 2 (GLUT2), glycogen synthesis (GS). It also down-regulated phosphorylated insulin receptor substrate-1 (p-IRS-1(ser)) and glycogen synthesis kinase-3β (p-GSK-3β). Overall, MO5 alleviated IR and increased glycogen synthesis through the PI3K/Akt pathway.